Upper secondary education in Iceland during the COVID-19 pandemic - Gestsdóttir, Súsanna Margrét; Ragnarsdóttir, Guðrún; Björnsdóttir, Amalía; Eiríksdóttir, Elsa (Menntavísindasvið Háskóla Íslands, 2021)
As in other parts of the world, the COVID-19 pandemic had an extensive impact on the Icelandic education system. During the spring semester 2020 all upper secondary school buildings closed and teaching and learning was moved online overnight. This change which can be described as ‘emergency remote teaching’ (Bozkurt & Sharma, 2020) posed significant challenges for schools and teachers, requiring them to instantly adapt their teaching practices and course plans to a digital environment. The aim of the study is to investigate how upper secondary school teachers adapted and changed their teaching practices during the COVID-19 pandemic in the spring of 2020, their views on administrative support and impact on students. In May 2020, all upper secondary school staff were sent an electronic questionnaire on different aspects of working and teaching during the COVID-19 pandemic (Háskóli Íslands, n.d.). Here the focus is on the answers of upper secondary teachers to three categories of questions: (1) management and support during the transition to remote teaching; (2) changes made to teaching practices, such as teaching methods and assessment; and (3) impact on students, in terms of demands, participation, and homework. The answers provided are analyzed by school size (less than 250 students, 250–500 students, 501–1000 students, and more than 1000 students) as well as whether the teachers had any prior experience in distance education. Overall, 680 upper secondary school teachers answered the questionnaire (37% males, 57% were in the age bracket 40–59). The sample adequately reflects school population demographic characteristics, and the response rate was 42% of the overall number of upper secondary school teachers registered in The Association of Teachers in Upper Secondary Schools.The results showed that most teachers worked from home and said that they made changes to their teaching practices during the COVID-19 pandemic. Courses were rarely suspended and therefore teachers generally continued their teaching load, ...